Optimizing Student Learning Outcomes as Data Analysts through Capstone Project at RevoU Tech Academy - Wijaya, Cindy Ari (Jurnal Indonesia Sosial Sains, 2024)
Study Independen Bersertifikat Program Batch 6 at RevoU Tech Academy presents learning programs that focus on software engineering and data analysis. These two positions are considered important in today’s digital world. Apart from that, in order to improve the quality of human resources in the face of the complexity of the Industrial Revolution 4.0. This program will equip students to be ready to face the world of work with adequate knowledge and experience. The capstone project is one of the learning methods applied to evaluate student’s knowledge and hone their practical skills regarding software engineering and data analyst material. The Capstone Project in the Data Analyst module at this partner uses dataset from vending machine sales in Central New Jersey. In vending machine sales, it is known that in the 12 months in the 2022 period, the highest sales figure was owned by Gutten Plans at $6904 and the lowest was owned by Earle Asphalt at $1809. The methods of descriptive analysis, exploratory data analysis, and root cause analysis (RCA) are used in data analysis. As a component of the RevoU Tech Academy’s learning methodology, the Capstone Project demonstrates the critical role in developing human resources prepared to handle shifting industrial dynamics. In addition, students will receive pertinent knowledge and abilities to help them deal with the difficulties of the contemporary technological world.